1999
DOI: 10.1161/01.res.84.7.840
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Endothelial Nitric Oxide Synthase–Derived Nitric Oxide Is a Physiological Regulator of Myocardial Oxygen Consumption

Abstract: Abstract-Our objective was to determine the precise role of endothelial nitric oxide synthase (eNOS) as a modulator of cardiac O 2 consumption and to further examine the role of nitric oxide (NO) consumption in tissues taken from iNOS (Ϫ/Ϫ) (Ϫ28Ϯ4%), wild-type eNOS (ϩ/ϩ) (Ϫ22Ϯ4%), and heterozygous eNOS(ϩ/Ϫ) (Ϫ22Ϯ5%) but not homozygous eNOS (Ϫ/Ϫ) (Ϫ3Ϯ4%) mice. Responses to bradykinin in iNOS (Ϫ/Ϫ) and both wild-type and heterozygous eNOS mice were attenuated after NOS blockade with N-nitro-L-arginine methyl e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
111
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(128 citation statements)
references
References 45 publications
14
111
3
Order By: Relevance
“…It has been demonstrated that an acute bout of exercise enhances the production of NO, and thereby contributes to skeletal muscle vasodilatation [4,21]. NO is involved in cardioprotection [20], myocardial respiration [15,16], and in insulin-independent glucose uptake into the working muscle fibres [17]. This molecule also modulates the kinetics of oxygen consumption during exertion [29].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that an acute bout of exercise enhances the production of NO, and thereby contributes to skeletal muscle vasodilatation [4,21]. NO is involved in cardioprotection [20], myocardial respiration [15,16], and in insulin-independent glucose uptake into the working muscle fibres [17]. This molecule also modulates the kinetics of oxygen consumption during exertion [29].…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial respiration is under tonic inhibitory control of NO in accord with the finding that inhibition of NOS invariably increases mitochondrial oxygen consumption (28). Hence, insights into the topology of the enzyme in relation to the respiratory chain are crucial for understanding regulatory mechanisms of NO action.…”
Section: Discussionmentioning
confidence: 75%
“…It is known that Bk activates eNOS in endothelial cells by way of the B 2 receptors and decreases mitochondrial respiration (Loke et al 1999). Likewise, Ca 2+ ionophore III enhances the production of NO by calmodulindependent binding, thus lowering the respiration rate.…”
Section: Resultsmentioning
confidence: 99%
“…Previously reported studies have found that the activation of the NOS enzyme during oxygen consumption measurements in endothelial cells (Loke et al 1999;Palacios-Callender et al 2004) and cardiac myocytes (Dai et al 2001) reduced the V O 2 max and increased p50. However, the results obtained in the present studies for BAECs pre-incubated with NOS stimulators or inhibitors exemplify different results.…”
Section: Hsp90mentioning
confidence: 89%
See 1 more Smart Citation